Keterlibatan Karyawan Sebagai Variabel Pemediasi Pengaruh Persepsi Dukungan Organisasi Terhadap Kesiapan Untuk Berubah (Survei Pada Kantor Pos Pusat Purwokerto) - Rendy Rizky; Ratna Pujiastuti; Heri Setiawan (FEB UNWIKU PURWOKERTO, 2022)
This study examines employee involvement in mediating the effect of perceived organizational support on organizational readiness to change. Testing using multiple linear regression analysis and Sobel test. The research shows that perceived organizational support has a significant effect on employee engagement. Perceived organizational support has a significant effect on organizational readiness to change. Employee involvement has a significant effect on organizational readiness to change. Employee involvement mediates the effect of perceived organizational support on readiness to change. Referring to these conclusions, it can be implied that as an effort to continuously improve organizational readiness for change, the Purwokerto Central Post Office management needs to implement appropriate policies related to perceptions of organizational support and employee involvement. The results of this study indicate that the role of employee involvement in encouraging organizational readiness to change is very important.